Desain Ruang Belajar Roundtable (Meja Bundar) Dalam Peningkatan Keterampilan Sosial Siswa Sekolah Dasar - Evi Rizqi; Subaidah Subaidah (PGSD FKIP UPR, 2023)
Social skills are a type of skill that must be possessed by students at the elementary school level. Because it is very necessary for their future in social life. Through the design of the Roundtable study room, students are expected to have good social skills. This study aims to describe what types of study room designs can create social skills in elementary school students. Qualitative analysis of Elementary School Students in Wringinrejo IV using the Roundtable study room learning design that has been implemented. The findings reveal that the design of the Roundtable study room can create social skills for elementary school students, through activities that facilitate the exchange of information between students, provide feedback and discuss material between students and teachers. However, there were several elementary school students who felt exposed and uncomfortable, so they tended not to participate. It can be concluded that the Roundtable study room design can create social skills, and moreover it is supported by the use of educational technology. Recommendations and suggestions are very open for future research.